Pure Small Cell Carcinoma of Prostate in a Patient Presenting with Acute Urinary Retention: A Rare Case Report - Sezgin Okçelik; Elmas Özgün; Şakir Eser; Mehmet Polat; Muhammed Cihan Temel; Fatih Ozcelik (Journal of Clinical Case Reports and Images, 2020)
Small cell carcinoma of the prostate is a rare and highly aggressive subtype of prostate cancers. In this case report, we evaluated a patient applied our outpatient clinic with acute urinary retention, whose pathology reported as pure small cell carcinoma of the prostate. A 73-year-old male patient was admitted to our outpatient clinic with acute urinary retention. Digital rectal examination was normal. The PSA value was 1.81 ng/dl. Prostate size was 101 cc. Open prostatectomy was performed. The pathology of the patient was reported as pure small cell prostate carcinoma. Four cycles of etoposide and cisplatin chemotherapy were administered to the patient. The patient died 13 months later after the first diagnosis. We evaluated the pathological and clinical findings of small cell carcinoma of the prostate.
Keywords: Acute